A thousand miles to freedom : my escape from North Korea - Kim, Un-ju, 1986-; Falletti, Sebastien; Tian, David (New York : St. Martin's Press, 2015)
'Eunsun Kim was born in North Korea, one of the most secretive and oppressive countries in the modern world. As a child Eunsun loved her country...despite her school field trips to public executions, daily self-criticism sessions, and the increasing gnaw of hunger as the country-wide famine escalated. By the time she was eleven years old, Eunsun's father and grandparents had died of starvation, and Eunsun was in danger of the same. Finally, her mother decided to escape North Korea with Eunsun and her sister, not knowing that they were embarking on a journey that would take them nine long years to complete. Before finally reaching South Korea and freedom, Eunsun and her family would live homeless, fall into the hands of Chinese human traffickers, survive a North Korean labor camp, and cross the deserts of Mongolia on foot. Now, Eunsun is sharing her remarkable story to give voice to the tens of millions of North Koreans still suffering in silence. Told with grace and courage, her memoir is a riveting exposof North Korea's totalitarian regime and, ultimately, a testament to the strength and resilience of the human spirit'--
'First published in France by Editions Michel Lafon under the title Coree du Nord : 9 ans pour fuir l'enfer'--Title page verso.
Keywords: Kim, Un-ju, -- 1986-.; Escapes -- Korea (North).; Political persecution -- Korea (North).; Korea (North) -- Biography; Korea (North) -- Politics and government -- 1994-2011.; Korea (North) -- Social conditions